2023
DOI: 10.3390/cells12222589
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy Spectral Fingerprints of Biomarkers of Traumatic Brain Injury

Georgia Harris,
Clarissa A. Stickland,
Matthias Lim
et al.

Abstract: Traumatic brain injury (TBI) affects millions of people of all ages around the globe. TBI is notoriously hard to diagnose at the point of care, resulting in incorrect patient management, avoidable death and disability, long-term neurodegenerative complications, and increased costs. It is vital to develop timely, alternative diagnostics for TBI to assist triage and clinical decision-making, complementary to current techniques such as neuroimaging and cognitive assessment. These could deliver rapid, quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 192 publications
1
2
0
Order By: Relevance
“…Aromatic amino acids and peptide backbones were the biomolecules that most effectively discriminated FM from other rheumatic diseases [14,66]. It has also been reported that FM patients have abnormal plasma amino acid levels such as phenylalanine, proline, glycine, lysine, tryptophan, and tyrosine, which are related to human neuronal functioning [53,67,68]. These outcomes support the notion that plasma amino acids serve as a potential biomarker for diagnosis of FM.…”
Section: Discussionsupporting
confidence: 57%
“…Aromatic amino acids and peptide backbones were the biomolecules that most effectively discriminated FM from other rheumatic diseases [14,66]. It has also been reported that FM patients have abnormal plasma amino acid levels such as phenylalanine, proline, glycine, lysine, tryptophan, and tyrosine, which are related to human neuronal functioning [53,67,68]. These outcomes support the notion that plasma amino acids serve as a potential biomarker for diagnosis of FM.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, TBI is associated with an increase in mitophagy leading to the externalization of CL to the OMM, thereby eliminating mitochondrial damage and preventing neuronal death [92]. Interestingly, recent studies are investigating the detection of CL in animal and human biofluids like blood, urine, saliva, and tears for its potential role as a biomarker in diagnosing traumatic brain injury (TBI) [15,117].…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…Harris and colleagues employed RS-based detection to characterize a panel of 18 TBI-indicative biomarkers, encompassing both raw (human, animal, and synthetically derived) samples and their aqueous solutions. 135 Colorimetric paper lateral flow strips (PLFS) could have drawbacks their low sensitivity and susceptibility to interference from complex sample matrices like blood. To address these issues, a new PLFS has been developed, incorporating SERS for signal transduction.…”
Section: Liquid Biopsy Investigation For Brain Disorders Through Spon...mentioning
confidence: 99%